2005
DOI: 10.2337/diabetes.54.8.2343
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Increases in Uncoupling Protein 3 Augment Fatty Acid Oxidation and Decrease Reactive Oxygen Species Production Without Uncoupling Respiration in Muscle Cells

Abstract: Decreased uncoupling protein (UCP)3 is associated with insulin resistance in muscle of pre-diabetic and diabetic individuals, but the function of UCP3 remains unclear. Our goal was to elucidate mechanisms underlying the negative correlation between UCP3 and insulin resistance in muscle. We determined effects of physiologic UCP3 overexpression on glucose and fatty acid oxidation and on mitochondrial uncoupling and reactive oxygen species (ROS) production in L6 muscle cells. An adenoviral construct caused a 2.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 51 publications
9
140
1
1
Order By: Relevance
“…A recent hypothesis on the physiological role of UCP3 could help interpret the decrease in UCP3 expression during weight loss [41]. In fact, based on in vitro experiments, UCP3 has been proposed to be a factor that limits reactive oxygen species (ROS) production by facilitating fatty acid oxidation [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent hypothesis on the physiological role of UCP3 could help interpret the decrease in UCP3 expression during weight loss [41]. In fact, based on in vitro experiments, UCP3 has been proposed to be a factor that limits reactive oxygen species (ROS) production by facilitating fatty acid oxidation [41].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, based on in vitro experiments, UCP3 has been proposed to be a factor that limits reactive oxygen species (ROS) production by facilitating fatty acid oxidation [41]. Thus, the role of UCP3 would be to protect muscle tissue against lipotoxicity, rather than to regulate energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, overproduction of UCP2 by more than tenfold also decreased insulin secretion. Indeed, there is now evidence in several cell types that a moderate increase in UCP2 [34,39] or UCP3 [40,41] levels does not induce any sign of mitochondrial uncoupling. The results of the present study demonstrate that this could also be the case for pancreatic Fig.…”
Section: Discussionmentioning
confidence: 99%
“…UCP2 expression is induced through activation of peroxisome proliferator-activated receptor Swim training improves leptin receptor deficiency-induced obesity and lipid disorder by activating uncoupling proteins (PPAR ), which is involved in fatty acid oxidation (Mori et al, 2004). In L6 myotubes, overexpression of UCP3 specifically increases fatty acid oxidation (MacLellan et al, 2005). These findings suggest that UCPs may be involved in the energy homeostasis.…”
Section: Introductionmentioning
confidence: 86%
“…It is reported that UCP1 is responsible for energy expenditure whereas UCP2 and UCP3 are involved in the fatty acid oxidation Hesselink, 2002, 2004;Hesselink et al, 2003;Sell et al, 2004;MacLellan et al, 2005). Although the primary function of UCP2 and UCP3 is not the regulation of energy metabolism, they seem to influence energy balance metabolism as a secondary effect and may be important in the prevention and/or treatment of obesity.…”
Section: Discussionmentioning
confidence: 99%